ANALYSIS OF INVESTMENT SENSITIVITY IN RUSUNAWA TAMBAK WEDI CITY SURABAYA - Mawardianto, Hayadi Agus; Laksono Djoko Nugroho; Haris Muhammadun (International Journal Science and Technology, 2023)
Based on the Surabaya City RPJMD for 2021-2026, strategic issues in government affairs in the field of housing and residential areas focus on providing Rusunawa capacity which is not proportional to the number of applicants. To overcome this problem, the Surabaya City Government took the initiative to build Rusunawa Tambak Wedi in the City of Surabaya. This research aims to evaluate the amount of investment receipts and determine the acceptance limits, with the aim of minimizing risks in Rusunawa investment activities. The research results show that the Medium Tariff Structure 1, Lower Tariff Structure 1, and Lower Tariff Structure 2 are considered feasible if analyzed based on the Net Present Value (NPV), Internal Rate of Return (IRR), Benefit Cost Ratio (BCR), and Payback Period methods. (PP) but the Medium Tariff Structure 2 and the Upper Tariff Structure were declared unfeasible if analyzed using the same method. Sensitivity analysis shows that each Rusunawa rental rate structure has a different level of sensitivity to changes in variables, such as residential unit rental rates, management fees, and management fee subsidies provided by the Government.